2019
DOI: 10.1111/jvh.13187
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the potential prevention benefits of a treat‐all hepatitis C treatment strategy at global, regional and country levels: A modelling study

Abstract: The World Health Organization (WHO) recently produced guidelines advising a treatall policy for HCV to encourage widespread treatment scale-up for achieving HCV elimination. We modelled the prevention impact achieved (HCV infections averted [IA]) from initiating this policy compared with treating different subgroups at country, regional and global levels. We assessed what country-level factors affect impact. A dynamic, deterministic HCV transmission model was calibrated to data from global systematic reviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Our analysis supports modeling indicating that the WHO elimination targets are likely achievable among PWID if treatment is combined with harm reduction scale‐up 30 . Additionally, our analysis is consistent with studies indicating that fewer treatments are required if treatment is prioritized to PWID and/or PWID and those with cirrhosis or more advanced disease, as well as if harm reduction is provided in combination 22,31 .…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis supports modeling indicating that the WHO elimination targets are likely achievable among PWID if treatment is combined with harm reduction scale‐up 30 . Additionally, our analysis is consistent with studies indicating that fewer treatments are required if treatment is prioritized to PWID and/or PWID and those with cirrhosis or more advanced disease, as well as if harm reduction is provided in combination 22,31 .…”
Section: Discussionsupporting
confidence: 85%
“…This offers an opportunity to intervene, and potentially control transmission rates, before the burden becomes as prevalent among PWID as it has in developed countries. Targeting PWID in regions such as Sub-Saharan Africa and Asia has been shown to result in a much higher rate of averted infections compared to their more economically developed counterparts (Trickey et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple and expanded micro‐elimination efforts in different high‐risk groups could result in macro‐elimination on a country/regional basis. A study modelling the potential prevention benefit of a hepatitis C treatment‐for‐all strategy on global, regional and country levels was recently published . This study concluded that significant prevention benefits were obtained from the WHO treat‐all strategy, although there was more benefit per treatment when PWID were targeted …”
Section: Mathematical Modellingmentioning
confidence: 99%